Art in Progress A Philosophical Response to the End of the Avant-Garde - Doorman, Maarten (Amsterdam University Press, 2003)
In this challenging and erudite philosophical essay, the author argues that in art, belief in progress is still relevant, if not essential. The radical freedoms of postmodernism have had a crippling effect on art - more than ever before, art is in danger of becoming meaningless. Art can only acquire meaning through context, and the concept of progress is ideal as the primary criterion for establishing that context. History of art can be seen as a process of constant accumulation. Works of art comment on each other, enriching each other's meanings. These complex interrelationships lead to progress in both the sensibility of the observer and the significance of the works of art.